Relationships between genetic polymorphisms and anticancer drug cytotoxicity vis-àà-vis the NCI-60 panel. (September 2006) - Le Morvan, Valéérie; Bellott, Ricardo; Moisan, Franççois; Mathoulin-Péélissier, Simone; Bonnet, Jacques; Robert, Jacques
Introduction: The National Cancer Institute (NCI)-60 panel consists of 60 human tumor cell lines initially established for screening thousands of molecules for antiproliferative activity. It has been powerful for deciphering the relationships between anticancer drug cytotoxicity and cell molecular characteristics. We tested its potential interest for establishing relationships between the polymorphism of genes involved in drug metabolism and transport or in DNA repair, and drug cytotoxicity extracted from NCI databases.Methods: Using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) techniques, three frequent single nucleotide polymorphisms (SNPs) were analyzed: Lys751Gln in the Xeroderma pigmentosum complementation group D (XPD, ERCC2 ) gene, Asp1104His in the Xeroderma pigmentosum complementation group G (XPG, ERCC5 ) gene and Ile105Val in the glutathione S -transferase P1 ( GSTP1 ) gene.Results: The allelic frequencies of the variants were 33% for ERCC2, 23% for ERCC5 and 39% for GSTP1 . The ERCC2 polymorphism appeared to be a strong determinant of the in vitro cytotoxicity of most anticancer agents, with lower half maximal inhibitory concentration (IC50 ) values in variant homozygous lines than in common homozygous or heterozygous cell lines. Unexpectedly, the cytotoxicity of taxanes appeared markedly dependent upon the ERCC2 genotype, with threefold lower mean IC50 values in variant homozygous cell lines. The ERCC5 genotype appeared to be important only for taxanes, with fourfold higher IC50 values in variant homozygous cell lines. The GSTP1 polymorphism was related to the cytotoxicity of several drug classes, especially topoisomerase inhibitors, antimetabolites and N 7 alkylating agents.Conclusion: The NCI-60 panel is capable of providing clues and tracks for the establishment of clinically useful relationships between a given genotype and the cytotoxicity of an anticancer agent.